The Influence of Social Media Marketing and Electronic Word of Mouth on The Purchase Decision of AZKO Products in Surabaya - Raihano, Keanrafi Daffa; Izaak, Wilma Cordelia (Publikasi Inspirasi Indonesia, 2026)
Following the rebranding of Ace Hardware Indonesia to AZKO, the company faced challenges in maintaining sales performance amid increasingly competitive competition in the home appliance retail industry. This study was conducted to determine how Social Media Marketing and Electronic Word of Mouth (e-WOM) influence consumer purchasing decisions on AZKO products in Surabaya. This study is quantitative in nature with a non-probability sampling method using purposive sampling techniques to determine the sample from the population of consumers who know and have purchased AZKO products in Surabaya. A total of 110 respondents were involved in data collection through an online questionnaire. The data obtained was then processed and analyzed using the Partial Least Square (PLS) approach through SmartPLS software. Based on the analysis results, both hypotheses in this study were accepted, indicating that Social Media Marketing and Electronic Word of Mouth (e-WOM) have a positive and significant influence on consumer purchasing decisions. The conclusion of this study shows that purchasing decisions will increase along with the increasing effectiveness of marketing strategies through social media and e-WOM management implemented by AZKO, so that these two variables are important to maintain and improve.